Novel flaxseed mucilage-based probiotic film: Application to sheep Sicilian cheese preservation - Mahmoudi, Imen; Boulares, Mouna; Nabi, Sedki; Fattouch, Sami; Hassouna, Mnasser; Moussa, Olfa Ben (Acta Scientiarum. Technology, 2024)
Edible probiotic films incorporated by probiotics can be used to keep away from undesirable microbes on the surface of the cheese to improve its quality and promote beneficial effects on consumer health. In this study, flaxseed, Lactobacillus rhamnosus and Lactobacillus acidophilus as probiotics were used to produce active edible packaging and evaluate its application in the sheep Sicilian cheese surfaces stored 10 days at 4°C. Microbiological, physicochemical, sensorial quality, antibacterial and antioxidant effects of cheeses were studied. The flaxseed mucilage-probiotic film improved cheese preservation by reducing the weight loss, preserving the pH and colour. Advantageously, flaxseed coating allowed improving probiotic viability throughout storage period. Native microbiota counts remained under safe levels. Probiotic coating cheeses exhibited 12.8±0.25 mm of maximum diameter inhibition against Listeria monocytogenes and enhanced oxidation (maximum DPPH inhibition: 51±0.33%) with acceptable sensorial properties for consumers. Hence, flaxseed mucilage probiotic film has proved to be suitable for quality preservation of functional foods.